Women editors presence in Spanish audiovisual media - Lara Martínez, María; Lara Martínez, Antonio; García-Castillo, Noelia (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Analysis of the audiovisual editing field in Spain. The methodology used has been the documentary analysis and statistical analysis with the SPSS software, of the AMAE (Association of Audiovisual Editors of Spain) database, of 388 members, about gender issues such as discrimination and harassment, remuneration and conciliation. The result is a less egalitarian representation than what might be expected, since the data reveals that the percentage of women editors barely exceeds a third (among the different positions) of the total number of people participating in the study.